PERLINDUNGAN DAN HAK KORBAN KEKERASAN DALAM RUMAH TANGGA PERSPEKTIF HUKUM ISLAM DAN HUKUM PIDANA - Fitria Amania; Budi Sastra Panjaitan, Najwa Khalilah Harahap, Lafifah Ulfah Dalimunthe, Andrew Hermawan Harahap, Mu (INTELIGENSIA MEDIA, 2025)
This study discusses the form of protection provided by law to women who are victims of domestic violence (KDRT) which of course is seen and reviewed from the perspective of Islamic Law and Criminal Law in Indonesia. This study is certainly something that can be highlighted because it is so relevant to things that are happening today, some of the things that are the objectives are to be able to understand the discussion of domestic violence (KDRT) according to Islamic Law and Criminal Law. In addition, it is also to provide access to protection in building a household so that it becomes a harmonious and mutually protective family. In the event of domestic violence (KDRT) there is certainly a motive that underlies this so that the family becomes disharmonious and messy, these things are mostly caused by good communication, economic problems, differences of opinion, culture and culture. In addition, it is also a fairly large driving factor regarding infidelity. Every act certainly has an impact that is the end of the problem that occurs and this not only has a short-term impact but will certainly have a long-term impact as well. Then the object of research used in this study is the concept of domestic violence regulated in criminal law (UU PKDRT) and also Islamic Law. The form of protection provided by law is regulated in temporary protection from the police, court protection and placement of victims in